'Human emancipation and the problem of violence': modern programme, state and education*. Issue 4 (8th August 2018) - Scalon, Roberto F.
ABSTRACT: This essay asserts that the intellectual and moral attitude that legitimates, justifies and ennobles violence derives from the fact that the evolution of modern philosophical history has been dominated by the 'rationalist' paradigm (versus the 'ontological' one). This process is clarified by reference to four European scholars, whose analysis is different but in many respects analogue: Huizinga, Del Noce, Eisenstadt, and Spaemann. The triumph of violence and injustice (in the form of coercion as a-normativity) in late modern societies demonstrates the failure of this paradigm; and its failure perhaps provides an opportunity for the realist/ontological paradigm to strengthen its position.